Growth-enhancing economic freedom. Issue 2 (2nd May 2017) - Ghosh, Sriparna; McCannon, Bryan C.
Abstract : Purpose: We explore how economic freedom measurements can be used to guide policy. Design/methodology/approach: We propose a method for creating a growth-enhancing economic freedom index, which allows for nonlinearities and interaction effects between the components to economic freedom. We use this method to illustrate that US states differ in which policy area generates the greatest gains. Findings: To validate the method presented, we apply our index to state bond markets. Financial market participants have the incentive to properly evaluate states' policies. If our measurement is useful, then it should correlate with bond ratings. Consistent with this hypothesis, we present evidence that state bond ratings are strongly correlated with our growth-enhancing economic freedom index. Originality/value: It has been well-established that economic freedom is associated with good economic outcomes. Economic freedom is comprised of numerous dimensions. Thus, the marginal benefit of improving policy in one area can be expected to depend on the amount of freedom in the other dimensions. Which policy improvement is most impactful depends on the entire menu of current policies and, therefore, differs between states. Our new method can then be used as a guide to determining for a particular state which policies can be expected to impact economic well-being the most.